Prevalensi dan Distribusi Penderita Geographic Tongue pada Mahasiswa Fakultas Kedokteran Gigi Universitas Jember Angkatan 2014 – 2016 (Prevalence and Distribution of Geographic Tongue in Faculty Of Dentistry University of Jember Class of 2014-2016) - Pratita Ayu Pinasthika; Ayu Mashartini P; Ristya Widy E Y (Pustaka Kesehatan, 2018)
Background: Geographic tongue is a tongue disorder. The lesion is a asymptomatic and rarely lesion. These disorder is influenced by genetic and other predisposing factors. Previous studies had shown geographic tongue occured more frequently in female than male, in these study will be disscused how the prevalence and distribution by age and gender. Objective: To determine the prevalence and distribution of geographic tongue of University Students in Faculty of Dentistry University of Jember class of 2014-2016. Method: Was used descriptive epidemiology and the results presented in table and would be described. Result and Conclusion: Results showed the prevalence was 14 patients from 324 subjects or 4,3%. The results showed higher in female than male and higher in 18 years old. Keywords: Distribution, geographic tongue, prevalence.